Crowding-out Of Household Expenditure By Tobacco In Ghana - Masa-ud, Abdul Gafar Abubakar (School of Economics, 2020)
This paper examines whether other expenditure in Ghanaian households is crowded out by expenditure on tobacco over the period under study (2005/2006 and 2012/2013) and whether the magnitude of crowding-out over the period has been changed by the introduction of the tobacco control law in July, 2012. The paper uses household survey data from the Ghana Living Standards Survey in the years 2005/2006 and 2012/2013. A system of quadratic conditional Engel curves was estimated for a set of eleven groups of commodities for both periods. The results show a crowding-out of food, alcohol, clothing and transport and a crowding-in of furnishings, health and communication expenditure by tobacco. The magnitude of crowding-in and crowding-out declined over the period under study. The tobacco control law of 2012 was positively associated with a reduction in the prevalence rate of tobacco use among households, and a reduction in household budget share allocation to tobacco.